2001
DOI: 10.1007/pl00013992
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Levels of γ-Aminobutyric Acid and Glutamate Decarboxylase in Developing Soybean Seedlings

Abstract: The changes in the levels of 7-aminobutyric acid (GABA), glutamic acid (Glu), calcium ions, and calmodulin as well as glutamate decarboxylase (GAD) activities were investigated in developing soybean seedlings. The GABA level determined was 12.3% of total free amino acids in the apical regions of roots, whereas it was only 4.2% of total free amino acid in cotyledons. The apical regions of roots also contained significantly higher levels of GAD, compared with cotyledons and mature base tissues. The Glu level was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 23 publications
2
16
0
1
Order By: Relevance
“…The role of Gaba in plants is not fully understood but it has been suggested that its accumulation might be a part of an adaptive response associated to cytoplasmatic acidosis (Crawford et al, 1994). However, the decrease in the cytoplasmatic pH is not a pre-requisite for the Gaba synthesis (Oh & Choi, 2001). Several stressing factors which are associated with the Gaba synthesis are also involved in the increase in the levels of cytosolic Ca 2+ (Bown & Shelp, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…The role of Gaba in plants is not fully understood but it has been suggested that its accumulation might be a part of an adaptive response associated to cytoplasmatic acidosis (Crawford et al, 1994). However, the decrease in the cytoplasmatic pH is not a pre-requisite for the Gaba synthesis (Oh & Choi, 2001). Several stressing factors which are associated with the Gaba synthesis are also involved in the increase in the levels of cytosolic Ca 2+ (Bown & Shelp, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…The supernatant in the upper layer was collected and then 800 ll of 70% ethanol was added to the pellet, the extraction process was repeated three times. The supernatant was collected and combined with the first supernatant (Baum et al 1996;Oh and Choi 2001;Komatsuzaki et al 2007). The obtained crude extract containing GABA was then passed through the 0.45 lm filter and analyzed by HPLC and LC-MS techniques after 2-hydroxynaphthaldehyde (HN) derivatization.…”
Section: Gaba Extractionmentioning
confidence: 99%
“…Many methods used in previous reports have attempted to increase GABA levels in rice, for example by using biotechnology methods such as transferring GAD genes for the higher GABA production (Park and Oh 2006), fermentation methods for the conversion of glutamic acid substrate to GABA (Kono and Himeno 2000;Su et al 2003;Chen et al 2006;Huang et al 2007) and other methods which include rice germination (Oh and Choi 2001;Komatsuzaki et al 2007;Xing et al 2007). …”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…콩나물의 발아과정에서의 부위별 GABA의 함량을 측정한 연 구에서는 뿌리 끝의 총 유리 아미노산 (free amino acids) 중 GABA의 함량이 12.3%를 차지하고 있었고, 떡잎의 총 유 리 아미노산 중에는 4.2%를 차지하였으며, GAD 또한 떡잎 이나 다른 부위의 조직에 비해 뿌리 끝에서 아주 높은 활성을 보임이 보고되었다 (Oh and Choi, 2001). 빛은 에너지의 1차적 소스로써 식물에게 매우 중요하며, 광도나 광질, 그리고 광주기는 식물의 발달과 높은 광합성 효 율의 상당 부분을 조절한다 (Hangarter, 1997 Co., Japan)를 이용하여 5반복으로 측정하였다 (Hwang and Park, 2011 (Fig.…”
unclassified